Use of interim execs as a nontraditional model. Issue 6 (11th November 2019) - Fisher, Mike
Abstract : Purpose: The purpose of this article is to define the use of interim executives in the workplace. Design/methodology/approach: A thought leadership approach is adopted for this article. Findings: The article describes the common misconceptions, potential pitfalls and the benefits of hiring an interim executive. Originality/value: At a time of changing work practices, economic and political uncertainty, organisations require help, without delay. This article offers an interim management solution as a way of assisting organisations to transform.